Cash-based aid and civil war violence: New evidence from Myanmar (2012–2020) - Hyun Jin Choi; Jiyoun Park (Research & Politics)
Why do some aid projects in conflict environments improve the welfare of local communities and reduce insurgent violence, whereas other projects place them in greater danger? This study investigates this question by testing the effects of aid projects on the intensity of civil war using subnational data on violence and service provision in Myanmar (2012–2020). We find that small-scale, cash-based aid projects significantly reduce battlefield violence at the township level, and the effects of such projects are larger than those of other projects aimed at reducing violence (e.g., peacebuilding). These results provide support for recent counterinsurgency theories, which argue that smaller projects can reduce violence by motivating civilians to share information about rebels with the government (or pro-government) forces. This analysis offers a unique insight into the way cash-based services, though small and relatively inexpensive, can foster stability in conflict zones and save more lives.